The Enigma of Shadows: Cast Shadow as a Measure and Presence of the Other (Itinera, 2023)
Shadow, a physical phenomenon that we experience every day and is intuitively easy to understand, does not seem to hide great mysteries. However, through the study of texts and works of Western figurative art, a different reality linked to its use can be observed. In fact, the presence of shadow in Western art and representation is profoundly discontinuous and non-linear, and it does not become more frequent with a greater mastery of representation techniques. There are authors who were knowledgeable about and studied the phenomenon in detail but nonetheless advised against its use or avoided it altogether.For these reasons, we have decided to delve into the use and representation of shadow in figurative art and its significance, focusing specifically on two distinct artistic techniques. The objective of this article is to demonstrate: 1) that the use of shadow in figurative art and representation is not simply a coincidental fact or a mere attempt to imitate reality, but rather reveals a specific conscious intention of the artist to represent; 2) that there is a difference in the use of cast shadow, particularly regarding the presence or absence of the subject casting the shadow within the framed and represented scene.To support this thesis, an interdisciplinary analysis of two examples is conducted, one from painting and one from cinema. However, due to the vastness of the time span and examples, it was necessary to narrow down the scope of research by limiting the analysis to two examples from the 20th century in painting and cinema: Giorgio de Chirico (1888 – 1978) and Ingmar Bergman (1918 – 2007).
Keywords: Shadow, Cinema, Painting, De Chirico